Unusual cause of subluxation of Austin Moore prosthesis of the hip (Journal of Science and Technology, 2016)
Subluxation and dislocation following hip arthroplasty is a well known complication. It can be due to a number of reasons - varying from malrotation of the component, operative approach, previous surgery, previous stroke, loosening and high wear rates of prosthesis, infection to even patient behaviour. In this study, an unusual cause of subluxation of the hip caused by impinging tissue - prolapsed fat is reported in an 88 year-old female in a Northern England hospital. Post-operative check x-rays showed a subluxed Austin Moore propthesis. It was successfully surgically corrected. In a large number of cases of subluxations, no cause can be found. Re-operations have been found to be most successful when a precise determination of the cause of instability is made and appropriate measures applied.